In vivo and in vitro assessment of the role of glutathione antioxidant system in anthracycline-induced cardiotoxicity - Vávrová, Anna; Popelová, Olga; Stěrba, Martin; Jirkovský, Eduard; Hašková, Pavlína; Mertlíková-Kaiserová, Helena; Geršl, Vladimír; Simůnek, Tomáš (Archives of toxicology, 2011)
The clinical usefulness of anthracycline antineoplastic drugs is limited by their cardiotoxicity. Its mechanisms have not been fully understood, although the induction of oxidative stress is widely believed to play the principal role. Glutathione is the dominant cellular antioxidant, while glutathione peroxidase (GPx) together with glutathione reductase (GR) constitutes the major enzymatic system protecting the cardiac cells from oxidative damage. Therefore, this study aimed to assess their roles in anthracycline cardiotoxicity. Ten-week intravenous administration of daunorubicin (DAU, 3 mg/kg weekly) to rabbits induced heart failure, which was evident from decreased left ventricular ejection fraction and release of cardiac troponins to circulation. However, no significant changes in either total or oxidized glutathione contents or GR activity were detected in left ventricular tissue of DAU-treated rabbits when compared with control animals. GPx activity in the cardiac tissue significantly increased. In H9c2 rat cardiac cells, 24-h DAU exposure (0.1-10 μM) induced significant dose-dependent toxicity. Cellular content of reduced glutathione was insignificantly decreased, oxidized glutathione and GR activity were unaffected, and GPx activity was significantly increased. Neither buthionine sulfoximine (BSO, glutathione biosynthesis inhibitor) nor 2-oxo-4-thiazolidine-carboxylic acid (OTC, glutathione biosynthetic precursor) had significant effects on DAU cytotoxicity. This contrasted with model oxidative injury induced by hydrogen peroxide, which cytotoxicity was increased by BSO and decreased by OTC. In conclusion, our results suggest that the dysfunction of glutathione antioxidant system does not play a causative role in anthracycline cardiotoxicity.
Keywords: thiazolidiny; modely u zvířat; buněčné linie; Glutathione; Hydrogen Peroxide; Pyrrolidonecarboxylic Acid; Thiazolidines; Oxidative Stress; Daunorubicin; glutathionperoxidasa; Antibiotics, Antineoplastic; Cell Line; srdce; krysa rodu Rattus; vztah mezi dávkou a účinkem léčiva; glutathionreduktasa; králíci; Buthionine Sulfoximine; Dose-Response Relationship, Drug; protinádorová antibiotika; Glutathione Peroxidase; antioxidancia; peroxid vodíku; Heart; Models, Animal; mužské pohlaví; Glutathione Reductase; zvířata; daunomycin; glutathion; oxidační stres; Rabbits; Animals; Rats; Male; buthionin sulfoximin; Heart Diseases; Antioxidants; nemoci srdce; kyselina pyrrolidonkarboxylová